AI Ethics in Business – A Bibliometric Approach - Alexandru Constantin Ciobanu (Review of Economic and Business Studies, 2021)
Different businesses utilize Artificial intelligence (AI) to accelerate their digital transformation aiming to enhance specific outcomes while maximize productivity. Artificial Intelligence technologies have evolved rapidly and the interest to study this field has increased accordingly. In this context, the researchers were interested not only on the technical side of AI, but also on its impact on economy, or business. This study reviews, trough bibliometric techniques, the key players, and the main discussed topics, that contribute to the research of ethics of AI solutions implemented in business. We analyzed the most cited 2000 articles extracted from Scopus databases, and we used VOSviewer to visualize the identified data. The insights provided through this paper are valuable for the researchers that are exploring the AI ethics, as well as for specific audiences from different domains such as social sciences, business decision making, IT management, government, and public policy decision-makers.